Working toward Healthy and Sustainable Diets: The “Double Pyramid Model” Developed by the Barilla Center for Food and Nutrition to Raise Awareness about the Environmental and Nutritional Impact of Foods - Ruini, Luca Fernando; Ciati, Roberto; Pratesi, Carlo Alberto; Marino, Massimo; Principato, Ludovica; Vannuzzi, Eleonora (Frontiers in Nutrition, 2015)
The Barilla Center for Food and Nutrition (BCFN) has produced an updated version of the traditional Food Pyramid based on the Mediterranean Diet in order to assess the simultaneous impact that food has on human health and the environment. The Double Pyramid model demonstrates how the foods recommended to be consumed most frequently are also those exerting less environmental impact, whereas the foods that should be consumed more periodically are those characterized by a higher environmental impact. The environmental impacts resulting from three different menus were compared. All menus were equally balanced and comparable in terms of nutrition, but they differed in relation to the presence of absence of animal flesh and animal products. The first dietary pattern (omnivorous) included both animal flesh and products; the second (lacto-ovo-vegetarian) included animal products (eggs and dairy) but no flesh; and the third (vegan) was solely plant-based. The results obtained suggest that a diet based on the principles of the Mediterranean Diet, as suggested by the Double Pyramid, generates a lower environmental impact compared to diets that are heavily based on daily meat consumption